Stirring the Deep, Disentangling the Complexity: Report on the Third Species of Thermochiton (Mollusca: Polyplacophora) From Haima Cold Seeps - Wang, Hao; Liu, Huijie; Wang, Xiaowei; Zhang, Junlong; Sirenko, Boris I.; Liu, Chuanyu; Dong, Dong; Li, Xinzheng (Frontiers in Marine Science, 2022)
This study documents a new deep-sea chiton from the Haima cold seeps. Thermochiton xui. nov. is the third species of the genus Thermochiton and the first occurrence of this genus in the South China Sea. This species is identified by its morphological characteristics and the molecular sequence of a Thermochiton species is reported for the first time. The placement of the new species is determined in the phylogenetic tree of Ischnochitonidae by Maximum Likelihood (ML) and Bayesian inference (BI) methods, based on the sequences of the mitochondrial cytochrome c oxidase subunit I (COI), 16S ribosomal DNA (16S), and nuclear 28S ribosomal DNA (28S) gene regions. Bayesian evolutionary analysis with an uncorrelated relaxed clock approach indicated that this new species is estimated to have diverged from its most closely related shallow-water ischnochitonid taxa 5.10–10.07 million years ago in the Late Miocene. A regional ocean general circulation model was used to estimate the potential dispersal ability of the three species of Thermochiton. Because it is highly unlikely for one species to have spread between the northwest and southwest Pacific to the localities in which this genus has been found to date, we propose that ‘stepping-stone’ habitats and/or ‘bridge species’ were involved in the dispersal and evolution of these cold-seep endemic chitons. The ZooBank Life Science Identifier (LSID) for this publication is: urn:lsid:zoobank.org:pub:AD93E4BC-2977-405E-B681-D956C5C66D83. And the ISID for Thermochiton xui sp. nov. is: urn:lsid:zoobank.org:act:0C75D2E3-F30E-4970-9BC2-3363B397720C.